2011
DOI: 10.1007/s12185-011-0838-3
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the standard dose of imatinib, rather than dose adjustment based on its plasma concentration, is critical to achieve a deep molecular response in patients with chronic myeloid leukemia

Abstract: The correlation between imatinib (IM) trough plasma concentration (Cmin) and clinical response was assessed in patients with chronic-phase chronic myeloid leukemia. The Cmin correlated with neither the achievement of complete cytogenetic response (977 vs. 993 ng/ml, P = 0.48) nor a major molecular response (1,044 vs. 818 ng/ml, P = 0.17). Although this was significantly higher in patients with complete molecular response (CMR) than in those without (1,430 vs. 859 ng/ml, P = 0.04), the difference was not signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Eight publications came from Europe, 14,15,18,19,21,24,25,30 5 from the US, 20,23,[31][32][33] 5 from Asia 22,26,28,29,35 and one from Australia.…”
Section: Literature Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight publications came from Europe, 14,15,18,19,21,24,25,30 5 from the US, 20,23,[31][32][33] 5 from Asia 22,26,28,29,35 and one from Australia.…”
Section: Literature Searchmentioning
confidence: 99%
“…14,15,22,24,25,35 In the prospective Adherence Assessment with Glivec: Indicators and Outcomes (ADAGIO) study, Noens and colleagues 14 showed that, on average, patients with suboptimal response had significantly higher mean percentages of imatinib not taken than did those with optimal response: 23% versus 7% using pill count ( Figure 5A). …”
Section: The Consequences Of Non-adherencementioning
confidence: 99%
See 3 more Smart Citations